Menggugat politik Orde Baru - Haris, Syamsuddin, 1957- (Jakarta : Pustaka Utama Grafiti, 1998)
Political conditions in Indonesia; articles.
Includes bibliographical references and index.
Keywords: Indonesia -- Politics and government -- 1998-